Hidrophile-lipophile balance and solubility parameter of cationic surfactants - Proverbio, Zulema E. (2003)
By using hydrophile–lipophile balance (HLB) values of cationic surfactants obtained from literature, two methods to determine this property were tested to verify if they are applicable to such amphiphiles: Little's method with the surfactant solubility parameter (δ) and the water number of Greenwald et al., related to their ability to promote inversion of emulsions. Cationic surfactants did not follow the behaviour of anionic and non-ionic surfactants. Little's method gave non-realistic values of HLB for cationic surfactants, whereas the Greenwald et al. treatment gave a non-linear relationship. However, both δ and water numbers are related with the HLB values, but these relations are different from those for anionic and non-ionic surfactants. This is not surprising on dealing with water number (anionic and non-ionic surfactants follow different equations in the paper of Greenwald et al.), but in the case of δ, Little has shown that both, anionic and non-ionic surfactants, follow the same equation. The solubility parameters of dodecyltrimethylammonium and dioctadecyldimethymammonium bromides, and the HLB value of dodecylpyridinium chloride are reported.